Somatic Symptoms as Idioms of Distress in East Asian Patients With Differing Temporomandibular Disorder Diagnostic Subtypes - Adrian Ujin Yap; Sunghae Kim; Jung Hwan Jo; Byeong-min Lee; Ji Woon Park (International Dental Journal)
Objective: This cross-sectional study investigated the prevalence/severity of somatic symptoms, their relationship with psychological distress and oral behaviors in different temporomandibular disorder (TMD) diagnostic subtypes, and identified biopsychosocial factors associated with depression, anxiety, and jaw overuse behavior among East Asian patients. Methods: Anonymized data from consecutive new TMD patients at a tertiary oral medicine clinic were evaluated. TMD diagnoses were determined using the DC/TMD methodology, while somatic symptoms, depression, anxiety, and oral behaviors were assessed with the Patient Health Questionnaire (PHQ)-15, PHQ-9, Generalized Anxiety Disorder Scale-7, and Oral Behavior Checklist. Data were examined using the Chi-square/non-parametric tests and multivariate linear regression analysis (α = 0.05). Results: Among the 699 patients, somatic symptoms were present in 36.8%, 54.0%, and 48.2% of individuals with intra-articular (IT), pain-related (PT), and combined (CT) TMDs respectively. Significant differences in somatic symptom burden/depression (PT, CT > IT) and anxiety (CT > IT) were observed. For all TMD subtypes, patients with somatic symptoms showed significantly greater depression, anxiety, and jaw overuse behavior compared to those without somatic symptoms. Somatic symptoms were moderately correlated with depression and anxiety (rs = 0.51-0.65). Conclusion: Somatic symptom burden was linked to depression and anxiety, supporting the phenomenon of somatization across different TMD subtypes.